汽车直齿锥齿轮系统内外部激励数值模拟 - 李东兵; 赵宇 (Jixie Chuandong, 2014)
In order to work on the car differential straight bevel gear system features further study,taking the automobile differential straight bevel gear as study object,by using the finite element method for static analysis model of internal excitation to make contact analysis,and the stiffness excitation,position of the tooth meshing,the relative speed of the driving gear and driven gear of the system are obtained,the numerical simulation of its meshing impact characteristic is carried out,the system engages impact excitation is got and harmonic excitation function is used to simulate system error.External excitation is the main consideration for the engine torque fluctuations and external vibrations,so that further analysis of the conditions fit the actual working conditions.